Physical Activity as a Central Pillar of Lifestyle Modification in the Management of Chronic Musculoskeletal Pain: A Narrative Review - Rodrigo Núñez-Cortés; Joaquín Salazar-Méndez; Jo Nijs (Journal of Functional Morphology and Kinesiology, 2025)
Objective: This narrative review aims to analyze physical activity as a central pillar of lifestyle modification in the management of chronic musculoskeletal pain by examining its effects on pain modulation as well as related lifestyle domains, including sleep, stress regulation, dietary habits, and smoking behavior. Methods: A narrative structured review was conducted. We searched MEDLINE/PubMed, Embase, and Cochrane Reviews using terms related to chronic pain and lifestyle. Randomized controlled trials, observational studies, systematic reviews, and narrative reviews reporting on the concepts of interest were included. The results were synthesized and described narratively. Results: Through the release of neuromodulatory compounds such as endorphins, endocannabinoids, dopamine, and serotonin, exercise improves analgesia, promotes emotional resilience, and reduces the reward response associated with addictive behaviors such as smoking. Its effects on the hypothalamic–pituitary–adrenal axis reduce cortisol levels, while melatonin regulation promotes circadian synchronization and deeper sleep stages. In addition, exercise modulates appetite by increasing insulin sensitivity and altering hormones such as leptin and ghrelin, contributing to appetite control and energy balance. These mechanisms support a comprehensive approach to chronic pain management. Conclusions: Physical activity is a core component of lifestyle-based chronic pain management, not only because of its analgesic effects, but also because of its positive influence on sleep, stress regulation, dietary habits, and smoking reduction. Although the available evidence is promising, more randomized controlled trials are needed to examine the effects of exercise on other healthy lifestyle behaviors, such as stress reduction, dietary modification, and smoking cessation, to consolidate its role in the comprehensive prevention and management of chronic pain.